2008
DOI: 10.1002/jez.488
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of growth rate and metabolism in Daphnia magna populations from different thermal habitats

Abstract: The aim of this study was to evaluate the effect of temperature on growth and aerobic metabolism in clones of Daphnia magna from different thermal regimes. Growth rate (increment in size), somatic juvenile growth rate (increment in mass), and oxygen consumption were measured at 15 and 25 degrees C in 21 clones from one northern and two southern sites. There were no significant differences in body size and growth rate (increase in length) at both 15 and 25 degrees C among the three sites. Clones from southern s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…For example, Mitchell & Lampert [25] observed that southern clones have a higher growth rate at 20-238C, but do not differ from the northern clones in the shape of growth rate reaction norm, which led them to conclude that among-population differences are not a manifestation of local adaptation. Chopelet et al [24] found evidence of higher oxygen consumption by southern clones at higher temperatures and vice versa, but this correlation was evident for only one of the two southern locations they sampled. Thus, local thermal adaptation and its possible mechanisms have been elusive in Daphnia studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, Mitchell & Lampert [25] observed that southern clones have a higher growth rate at 20-238C, but do not differ from the northern clones in the shape of growth rate reaction norm, which led them to conclude that among-population differences are not a manifestation of local adaptation. Chopelet et al [24] found evidence of higher oxygen consumption by southern clones at higher temperatures and vice versa, but this correlation was evident for only one of the two southern locations they sampled. Thus, local thermal adaptation and its possible mechanisms have been elusive in Daphnia studies.…”
Section: Discussionmentioning
confidence: 89%
“…Among them, studies of geographical variation in Daphnia have provided evidence for both phenotypic plasticity and genetic population differentiation [22][23][24][25]. However, despite ample genetic variation among genotypes and populations, no evidence for local adaptation was found in this system.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used a simple and cost-effective technique (MSP-PCR), which allowed satisfactory discrimination of genotypes (clones), analogously to RAPD (e.g., Weber and Declerck, 1997), microsatellite (e.g., Chopelet et al, 2008), or allozyme (e.g., Weider and Hebert, 1987) analyses. However, a conservative approach was needed, both in terms of band profile analysis and dissimilarity cut-off level, in order to avoid false positives (i.e., scoring identical genotypes as distinct).…”
Section: Discussionmentioning
confidence: 99%
“…Since the classic Daphnia study in which the term ''reaction norm'' was first formulated (Woltereck 1909), a plethora of Daphnia reaction norm data has been obtained, including those on plasticity of morphological characters (e.g. Jacobs 1987; Spitze and Sadler 1996;Boersma et al 1998;Tollrian and Heibl 2004;Spanier et al 2010;Miyakawa et al 2010), life-history traits (Lynch 1980;Spitze 1992;Ebert et al 1993;Yampolsky and Ebert 1994;Spitze and Sadler 1996;Boersma et al 1998;Weetman and Atkinson 2004;Latta et al 2007;Chopelet et al 2008;Beckerman et al 2010) and tolerance to pollutants (Coors et al 2004;Messiaen et al 2010), which Daphnia exhibit in response to a wide variety of environmental factors, from temperature and food availability to the presence of predators, parasites or pollutants.…”
Section: Introductionmentioning
confidence: 99%